Reconstruction of Scientific Knowladge on the Shore of Sentani Lake Jayapura Using Local Knowledge of the Homfolowkhouw Tribe - Risamasu, Putu Victoria M.; Pieter, Jan (International Journal of Contemporary Sciences (IJCS), 2024)
This research aims to reconstruct natural science from the local wisdom of the Homfolowkhouw Tribe community which can be used in science learning. This type of research is qualitative phenomenological ethnoscience, set in communities living on the edge of Lake Sentani, the methods used are in-depth interviews, observation, and documentation. The reconstruction results show that ethnoscience originating from Homfolowkhouw communities on the edge of Lake Sentani can be implemented in science learning because it contains scientific science concepts. The results of ethnoscientific reconstruction were found in the use of traditional medicinal plants, applications in work tools, applications in arts, and applications in astrology and floating house technology on Lake Sentani.